Eureka! : European research universities and the challenges of the 21st century - Funnekotter, Bart; Blondeau, Thomas, 1978-2013 (Amsterdam University Press, 2005)
Reveals how members of the League of European Research Universities - Oxford, Cambridge, Milan, Leiden, Edinburgh, Geneva, Heidelberg, Helsinki, Munich, Louvain and Stockholm - have dealt with government cutbacks in higher education, from appeals to the alumni, to increasing commercial R & D activities.